This preview has intentionally blurred sections. Sign up to view the full version.
View Full Document
Unformatted text preview: T ( n ± ) ≤ T ( n ) ≤ T ( n ±± ) 1. a < c , from the theorem T ( n ± ) = O ( n ± ) , T ( n ±± ) = O ( n ±± ) . ∴ T ( n ) = O ( n ) . 2. a = c , T ( n ± ) = O ( n ± log n ± ) T ( n ±± ) = O ( n ±± log n ±± ) . ∴ T ( n ) = O ( n log n ) . 3. a > c , T ( n ± ) = O ( n ± log c a ) , T ( n ±± ) = O ( n ±± log c a ) . ∴ T ( n ) = O ( n log c a ) . Therefore for any n , above theorem holds. 2...
View
Full
Document
This note was uploaded on 02/04/2010 for the course COMPUTER S cs300 taught by Professor Unkown during the Spring '08 term at Korea Advanced Institute of Science and Technology.
 Spring '08
 Unkown

Click to edit the document details